LINGUISTICS AND THE ENGLISH LANGUAGE INSTRUCTION - Syarif, Hermawati (English Department FBS UNP, 2016)
Linguistics as the scientific study of language has very crucial role in running language instruction. Changes in language teaching-learning method reflect the development of linguistic theories. This paper describes how the three broad views of linguistic theories, namely traditional grammar, generative grammar, and functional grammar work in relation to English language teaching and learning. Since both linguistics and language learning have the same subject to talk about, the knowledge of the language, then, is the core. Linguistic features analyzed are on the levels of Phonology, Morphology, Syntax, Semantics and Discourse as the basic components, supported by Psycholinguistics and Sociolinguistics. In relation to language teaching and learning, especially English, such knowledge on the English language gives learners the chance to apply in social communication and in any occasion. The use depends on the viewing of linguistic theories (English) in certain era, which reflects the need of learners in using English. It is assumed that the more linguistic competence someone has, the easier he/she can run his/her instructional activities. As the consequence, in the English language learning, the syllabus designer should notify the mentioned levels of linguistic components while constructing English instructional materials, methods, and evaluation based on the stage of learners to avoid misunderstanding in use. In this case, English instructors/teachers should also update their linguistic competence, especially on Psycholinguistic and Sociolinguistic points of view.Â Key words/phrases: linguistics, English, language instruction, linguistic competence